Faktor-faktor yang Mempengaruhi Financial Behavior - Paula Elicia; Indra Widjaja (Universitas Tarumanagara, 2021)
There are many factors that can affect individual life sustainability, both in short term and long term. One of the factors is decision to manage finance. The ability to manage the finance is not only to get sufficient income, but also the ability to manage finances more wisely and appropriately. The purpose of this research is to analyze the impact of Parental Influence, Financial Knowledge, Financial Attitude and Income on Financial Behavior. The population of this research is the clients of Bank BCA in Jakarta; who have earned income and have graduated with at least an S1 degree. The total sample is 298 respondents, were selected using convenience sampling method and data processing techniques used are taken from Structural Equation Modeling (SEM), that is supported by SmartPLS.3.3.2 program. The result of this study reveals that Parental Influence and Income has no significance influence on Financial Behavior; while Financial Knowledge and Financial Attitude do have a significance influence on Financial Behavior. Terdapat banyak faktor yang dapat mempengaruhi kelangsungan hidup individu, baik dalam jangka pendek maupun jangka panjang. Salah satu faktor diantaranya adalah keputusan dalam mengatur keuangan. Kemampuan dalam mengatur keuangan bukan hanya pada kemampuan untuk mendapatkan pendapatan yang cukup, melainkan juga kemampuan untuk mengelola keuangan secara bijak dan tepat. Tujuan penelitian ini adalah untuk menganalisa pengaruh Parental Influence, Financial Knowledge, Financial Attitude dan Income terhadap Financial Behavior. Populasi penelitian ini adalah nasabah dari Bank BCA di Jakarta yang sudah mempunyai penghasilan dan mempunyai tingkat pendidikan minimal S1. Sampel yang mencapai jumlah total 298 responden dipilih menggunakan metode convenience sampling. Teknik pengolahan data menggunakan Structural Equation Modeling (SEM) yang didukung oleh program SmartPLS.3.3.2. Hasil penelitian ini mengungkapkan bahwa Parental Influence dan Income tidak berpengaruh terhadap Financial Behavior; sedangkan Financial Knowledge dan Financial Attitude berpengaruh terhadap Financial Behavior.